Avaliação de empresas por fluxo de caixa descontado: o impacto dos ativos intangíveis no valor da empresa - Schiavo, Fabienne Torres (2008)
Intangibles assets have been widely discussed and presented as corporate successful conductors. At the same time, there are still few suggestions of how they can impact company value. This work has as main goal identify a way of considering intangibles assets when valuating companies through Discounted Cash Flow methodology. Twelve intangibles – brand, reputation, strategic alliance, human capital, intellectual capital, innovation, adaptability, corporate environment, leadership, social and environmental responsibility and communications and transparency - , were analyzed in order to find how they impact corporate economic value, and how they influence one another.